Minestrone Stories: Teaching anthropology through serendipitous cultural exchanges. Issue 2 (1st June 2020) - Kristensen, Regnar
Abstract: Serendipity should not be restricted to cutting-edge science and research alone. A proactive approach to the unexpected can also strengthen classes in anthropology and the humanities. But how can you teach if classes are influenced by accidental arrangements and discoveries not sought or considered? I shall tap into two projects of teaching-by-serendipity through indirect cultural exchanges. The two projects in question were named Minestrone Stories, referring to the Italian minestrone soup, usually made of the vegetables available and thereby providing each village in Italy with its own variant. However, the two 'Minestrone soups' in question included more ingredients. The teaching-by-serendipity projects targeted what students, teachers and citizens in confined areas of Copenhagen had available, inciting them to indirectly exchange vegetables, songs, services and stories with each other, thus stirring them together. In this article, I reflect on how this stirring provoked an unusual teaching experience and moments of unexpected learning.